Epidemiology of deaths related to stroke in the State of Paraná: a comparison between the years 2008 and 2018 (Research, Society and Development, 2020)
The large number of deaths related to stroke is one of the worldwide public health problems that deserves attention, as it is the second leading cause of mortality in the world and generates a large number of hospitalizations and disability in the affected individuals. This article sought to identify the epidemiological profile of deaths related to stroke in the years 2008 and 2018, regarding the age group, gender, ethnicity and place of death; this study was conducted in a retrospective, quantitative manner with data collection based on information made available in DATASUS, from the Brazilian Ministry of Health. Between 2008 and 2018, 69248 deaths due to cerebrovascular diseases were reported in the state of Paraná. Among these deaths, the majority affected males and white elderly people, which can be explained by the state's population being the majority of that race. We also observed that the most common place of death was hospitals, which culminates in the need for hospitalization of patients affected by this pathology, with a negative evolution. These epidemiological indices reflect, among other factors, the lack of adequate assistance in primary, secondary and tertiary care in the health system, and the knowledge of these data is of great importance for creating preventive measures for stroke patients, since many of the risk factors can be avoided, and therapeutic measures aimed at reducing the complications and disabilities caused by these diseases.